PERANCANGAN SEQUENCE PENAMBANGAN BATUBARA UNTUK MEMENUHI TARGET PRODUKSI BULANAN - Dadang Aryanda; Muhammad Ramli; H Djamaluddin (Jurnal Penelitian Geosains, 2014)
Sequence is mining forms that show how the pit will be mined from the first stage to the final stages of mine design (pit limit). The purpose of this study is to design sequences mining to monthly production target at Bara 14 Seam C. Plan production targets at this location is 40,000 tons of coal per month and a maximum stripping ratio is 15:1. Analysis data and research design sequence using software Minescape 4.118. The coal reserves which designed based on pit limit is 162,370 tons and 2,425,450 bcm of overburden material. The first sequence has an area of 4.97 ha mine openings with the amount of 40,000 tons of coal and overburden 599,990 bcm. Stripping ratio in this sequence is 15:1. The second sequence has a wide opening 8.44 ha mines the number of 40,000 tons of coal and overburden 599,900 bcm. Stripping ratio in this sequence is 15:1. The third sequence has an area of 11.67 ha mine openings with the amount of 40,000 tons of coal and overburden 599,520 bcm. Stripping ratio in this sequence is 15:1. The fourth sequence has extensive mine openings 11.67 ha with the amount of 40,000 tons of coal and overburden 599,330 bcm. Stripping ratio in this sequence is 15:1. The fifth sequence has extensive mine openings 11.67 ha with the amount of 2,370 tons of coal and overburden 26,710 bcm. Stripping ratio in this sequence is 11:1.Keywords: design, pit limit, sequence, stripping ratio, production target